COORDENADORES PEDAGÓGICOS: FORMADORES DE PROFESSORES OU SUPERVISORES DE AÇÕES POLÍTICO-PEDAGÓGICAS DA ESCOLA? - Nery, Josania de Lourdes Alcantarino (2012)
The educational system has suffered a direct influence of changes occurred in society that is increasingly exposed to a range of information that are not always transformed into knowledge. These changes vary from a new attitude of the teacher in the classroom to the schools social function itself, which still does not answer the needs of society. In this new scenario it is essential a best prepared teacher to guide the students, helping them to interact with others, to select the information that is exposed and transform them into knowledge, as well as interact with their peers. It is important to consider that student learning is directly related to teaching methods to which he is submitted. And to ensure that learning is necessary to have a team more prepared, more cohesive, aware of the work that is developing. So the partnership work between the pedagogical coordinator and teachers is necessary. But is the coordinator prepared for that? To learn how the pedagogical coordinator works in the continuing education of teachers, the research was carried out both theoretical and practical parts. In the theoretical framework are Alvaro Marchesi, Vitor Henrique Paro and Jose Carlos Libaneo, for their great contribution in the field of management; Antonio Nóvoa, Cleide Terzi, Laurinda Almeida and Vera Placco for their work on teacher training and pedagogical coordinators, besides masters and doctoral researches on this theme. In the practical part of the research is organized in view of the methodology qualitative / quantitative interviews with ten pedagogical coordinators. As the emphasis of the dissertation is to build the profile of professional life of the pedagogical coordinators, there were interviewed several segments (Early Childhood Education, Elementary and Secondary Education) from different schools (public and private network). In the quantitative survey, a questionnaire was administered to sixteen teachers, to learn the acting coordinator of the educational aspect of the trainer. The results showed that the pedagogical coordinator also needs training. He performs specific tasks that are not addressed either in universities or in specialized courses, there must be a partnership between the pedagogical coordinator and director of teaching and together decide the paths to be followed within the school, there must be a more directed to the staff meetings, meetings, lectures and activities planned, intentional, there is a need to give the teachers some feedbacks more often, closer, more active, the pedagogical coordinator needs to rethink the collective work, give their teachers the autonomy to act, within what is possible. Even the pedagogical coordinators who do not have autonomy within the school can do something to stop working with the brand of your direction, only with a partnership you can resolve conflicts and tensions and strengthen the leadership, the confidence of their peers the teamwork. Thus, the limitations of the pedagogical work surely diminish